ANALISIS KESIAPAN DOKTER KELUARGA SEBAGAI GATE-KEEPER PELAYANAN PESERTA BPJS DI WILAYAH KECAMATAN BANYUMANIK KOTA SEMARANG TAHUN 2014 - Akha Pratila Sari; Chriswardani Suryawati; Anneke Suparwati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
In the implementation of the National Health Insurance embracing the principles of Managed care, family doctors will be Gate-keeper. Acceleration Development Policy service of family doctors mention that problems that constrain the development of family doctors in Indonesia include hierarchical arrangements of health services and health financing system is not well organized. Family doctor in accordance Gate-keeper concept should be able to do the first level of screening referral to the second level and perform the quality control and cost control in accordance with the standards of physician competence. To prepare all forms of readiness as a family doctors Gate-keeper BPJS participants, it is necessary readiness to do. The purpose of this study was to Analysis of Family Doctor Readiness as Gate-Keeper BPJS Participant Services in Banyumanik District Semarang in 2014review of aspects of family doctor competence aspects, legal aspects, aspects of infrastructure, financing aspects and implementation aspects of the patient's health service. The research carried out to the family doctor on district Banyumanik on 8 people as the main informans head of primary service management BPJS as triangulation informant with the number 1 people BPJS participants as triangulation with 8 people. The Research used qualitative methods of collecting data through in depth interviews.The results showed that all key informants had competence in accordance with the Decree number 11 Perkonsil Medicine in 2012. For training Advance Trauma Life Support, Advanced Cardiac Life Support, endocrine and health,but there are still some key informants who have not followed the traing completely. Legal documents are complete. Disbursement of funds capitation always right is a maximum at the beginning of the 15th of the current month. Facilities and infrastructure have not completed, there are still some informants who do not provide TV, dispensers, refrigerators, fire extinguishers and sink. The service of chronis diseace management program have not done by all informant, it is due to the absence of such cases. Capitation financing of BPJS managed by family physicians, adequate for the health care participants